Learning Assistance by Tutors in Enhancing the Pedagogical Competence of In-Service Teachers - Supratman; Halidin; Arief Budi Wicaksono; Fitriyani Hali (LKP KARYA PRIMA KURSUS, 2026)
This article reports the implementation and outcomes of a community service program (PKM) conducted by 7th-semester students of the SALUT LAMOKATO Study Group, Universitas Terbuka (UT), designed to enhance the pedagogical competence of in-service teachers through a structured tutor-assisted learning model. The program was implemented at SMPN 1 Wundulako, Wundulako District, Kolaka Regency, Southeast Sulawesi Province, Indonesia, involving 26 in-service teachers as participants over eight weeks (October–November 2025). A quasi-experimental one-group pre-test–post-test design was employed, supplemented by classroom observation, reflective journals, and semi-structured interviews. The program targeted three key pedagogical dimensions: competency-based lesson planning, active learning strategy implementation, and authentic assessment design. Results of a paired-samples t-test revealed a statistically significant improvement in overall pedagogical competence (t(25) = 14.73, p < .001, Cohen’s d = 2.89), with the mean score rising from 54.8 to 77.6 a gain of 22.8 points bringing 84.6% of participants above the government-mandated proficiency threshold of 75. Qualitative findings identified four primary mechanisms of change: psychological safety in the tutor–teacher relationship, contextualized observational feedback, reflective journaling as metacognitive scaffolding, and institutional support from school leadership. The study affirms that structured tutor-assisted learning, implemented by trained UT students, constitutes an effective and scalable model for in-service teacher professional development in remote and underserved Indonesian educational contexts.